Biotransformation of 6:2 fluorotelomer alcohol by the whole soybean (Glycine max L. Merrill) seedlings. (February 2020) - Zhang, Hongna; Wen, Bei; Huang, Honglin; Wang, Sen; Cai, Zongwei; Zhang, Shuzhen
Abstract: Fluorotelomer alcohols (FTOHs) are important precursors of perfluorocarboxylic acids (PFCAs) in the environment and biota. With the growing application of 6:2 FTOH [F(CF2 )6 CH2 CH2 OH] in product formulation, it is becoming increasingly urgent to investigate its biological fates in different species. In this study, biotransformation of 6:2 FTOH by young soybean plants ( Glycine max L. Merrill) were investigated using hydroponic experiments. During the 144 h-exposure, 6:2 FTCA [F(CF2 )6 CH2 COOH], 6:2 FTUCA [F(CF2 )5 CFCHCOOH], 5:3 FTUCA [F(CF2 )5 CHCHCOOH], 5:3 FTCA [F(CF2 )5 CH2 CH2 COOH], PFHxA [F(CF2 )5 COOH] and PFPeA [F(CF2 )4 COOH] were phase I metabolites in soybean. At the end of exposure, 5:3 FTCA (5.08 mol%), PFHxA (2.34 mol%) and PFPeA (0.58 mol%) were three main metabolites in soybean-solution system. 5:3 FTCA was predominant in soybean roots and stems, while PFHxA was the most abundant product in leaves. PFBA [F(CF2 )3 COOH] and 4:3 FTCA [F(CF2 )4 CH2 CH2 COOH] detected in the hydroponic solution most-likely came from the transformation of 5:3 FTCA by root-associated microbes. Moreover, phase II metabolites of 6:2 FTOH were identified and monitored in soybean tissues. Alcohol dehydrogenase, aldehyde dehydrogenase and glutathione S-transferase were found to participate in 6:2 FTOH metabolism. Based on the phase I and phase II metabolism of 6:2 FTOH in soybean, this study for the first time provides evidences for the transformation pathways of 6:2 FTOH in plants. Graphical abstract: Image 1 Highlights: 6:2 FTOH could be taken up, translocated and biotransformed by soybean seedlings. 5:3 FTCA, PFHxA and PFHpA were main phase I metabolites in soybean. Phase II metabolites of GSH conjugates were identified in soybean. The enzymes of ALDH, ADH and GST took part in 6:2 FTOH metabolism in soybean. The transformation pathways of 6:2 FTOH in plants was proposed for the first time. Abstract : Phase I and phase II metabolites of 6:2 FTOH and some enzymic activities in soybean were analyzed, and possible biotransformation pathways were proposed.